Analysis of Factors Determining Customer Decisions Towards Purchasing Medan Cold N Brew Coffee Using Binary Logistic Regression - Eleonora, Eleonora; Jeslin Aurensia; Rosinta Romauli Situmeang; Mella Yunita (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to analyze the factors that influence customer purchasing decisions for Cold N Brew coffee products in Medan City. The independent variables studied include consumer behavior, price, and product quality. The method used in this study is a quantitative method with a binary logistic regression approach, where the dependent variable is binary (purchase or not purchase). Data were collected through distributing questionnaires to 50 respondents who are Cold N Brew customers. The results of the study indicate that partially and simultaneously, the three independent variables have a significant effect on purchasing decisions. The significance value of each variable, namely consumer behavior (0.002), price (0.001), and product quality (0.002), with a Nagelkerke R Square value of 0.437. This indicates that the model built can explain 43.7% of the variability in purchasing decisions, while the rest is influenced by other variables outside the model. Based on these results, Cold N Brew management is advised to continue improving product quality, adjusting pricing strategies, and building closeness with customers to strengthen loyalty and increase purchasing decisions.